Contribution of Physical Fitness, Socio-Economic Conditions and School Environment towards Academic Learning Achievement of Elementary School Students in North Semarang District 2019 (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study is to find out and analyze: 1) The contribution of physical fitness towards learning achievement, 2) The contribution of socio-economic conditions towards learning achievement, 3) The contribution of the school environment towards learning achievement, 4) The contribution of physical fitness and socio-economic conditions towards learning achievement, 5) The contribution of socio-economic conditions and school environment towards learning achievement, 6) The contribution of physical fitness and school environment towards learning achievement, and 7) The contribution of physical fitness, socio-economic conditions and the school environment towards learning achievement. This research is a quantitative study. The population is 393 students and 13 elementary schools. Data analysis techniques using multiple correlation analysis with Slovin formula. The results of the study revealed: 1) Contribution of physical fitness towards learning achievement is moderate with 43%, 2) Contribution of socio-economic conditions towards learning achievement is low with 43%, 3) Contribution of school environment towards learning achievement has incomplete criteria with 65%, 4) Contribution of physical fitness and socio-economic conditions towards learning achievement is 25%, 5) Contribution of physical fitness and school environment towards learning achievement is 67.5%, 6) Contribution of socio-economic conditions and school environment towards learning achievement is 67.5%, and 7) Contribution of physical fitness, socio-economic conditions and school environment towards academic learning achievement is 40%.